2022
DOI: 10.20408/jti.2021.0046
|View full text |Cite
|
Sign up to set email alerts
|

Age group analysis of patients with dog bite injuries who visited a single regional emergency medical center and factors affecting wound infections

Abstract: Purpose: The aim of this study was to analyze by age group the characteristics of patients with dog bite injuries, as well as determine which factors were associated with wound infections in those patients. Methods: We reviewed patients with dog bite injuries who presented to Gachon University Gil Medical Center in Incheon, Korea from January 1, 2014 to December 31, 2018. They were classified by age group: children (0–18 years), adults (19–59 years), or elderly (≥60 years). Event profiles, wound characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…It is reported that lesions are mostly superficial not requiring any sutures or surgical interventions, which are treated with local injury care with simple medical treatment. [ 21 , 23 , 29 ] In our study, we found that superficial injuries were common at a rate of 54.4% and simple medical treatment (localized wound care) was applied to 62.5% of our cases.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…It is reported that lesions are mostly superficial not requiring any sutures or surgical interventions, which are treated with local injury care with simple medical treatment. [ 21 , 23 , 29 ] In our study, we found that superficial injuries were common at a rate of 54.4% and simple medical treatment (localized wound care) was applied to 62.5% of our cases.…”
Section: Discussionmentioning
confidence: 66%
“…Along with this increase, injuries due to dog attacks are increasing day by day, and many health, economic, and legal problems arise with it. [ 4 , 5 , 7 , 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations